A mind to crime : the controversial link between the mind and criminal behaviour - Moir, Anne; Jessel, David (London : Michael Joseph, 1995)
A Mind to Crime shows how biology is a central factor in crime, interacting with cultural, social and economic factors.
Includes bibliographical references (pages 338-399) and index.
Keywords: Criminal psychology; Criminal psychology; Psychophysiology; Crimes -- Psychology